Endocardial-Myocardial Interactions During Early Cardiac Differentiation and Trabeculation - Qu, Xianghu; Harmelink, Cristina; Baldwin, H. Scott (Frontiers in Cardiovascular Medicine, 2022)
Throughout the continuum of heart formation, myocardial growth and differentiation occurs in concert with the development of a specialized population of endothelial cells lining the cardiac lumen, the endocardium. Once the endocardial cells are specified, they are in close juxtaposition to the cardiomyocytes, which facilitates communication between the two cell types that has been proven to be critical for both early cardiac development and later myocardial function. Endocardial cues orchestrate cardiomyocyte proliferation, survival, and organization. Additionally, the endocardium enables oxygenated blood to reach the cardiomyocytes. Cardiomyocytes, in turn, secrete factors that promote endocardial growth and function. As misregulation of this delicate and complex endocardial-myocardial interplay can result in congenital heart defects, further delineation of underlying genetic and molecular factors involved in cardiac paracrine signaling will be vital in the development of therapies to promote cardiac homeostasis and regeneration. Herein, we highlight the latest research that has advanced the elucidation of endocardial-myocardial interactions in early cardiac morphogenesis, including endocardial and myocardial crosstalk necessary for cellular differentiation and tissue remodeling during trabeculation, as well as signaling critical for endocardial growth during trabeculation.